2016
DOI: 10.1128/aem.01344-16
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradative Activities of Selected Environmental Fungi on a Polyester Polyurethane Varnish and Polyether Polyurethane Foams

Abstract: Polyurethane (PU) is widely used in many aspects of modern life because of its versatility and resistance. However, PU waste disposal generates large problems, since it is slowly degraded, there are limited recycling processes, and its destruction may generate toxic compounds. In this work, we isolated fungal strains able to grow in mineral medium with a polyester PU (PS-PU; Impranil DLN) or a polyether PU (PE-PU; Poly Lack) varnish as the only carbon source. Of the eight best Impranil-degrading strains, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(130 citation statements)
references
References 40 publications
(53 reference statements)
3
121
0
6
Order By: Relevance
“…The strain involving the most significant weight loss on TPU is the strain of Penicillium section Lanata‐Divaricata. Isolated species of Penicillium have been described on PU degradation studies such as Penicillium chrysogenum (Alvarez‐Barragan et al ., ), but to the best of our knowledge, no isolated strains of Penicillium belonging to the section Lanata‐Divaricata has been reported to degrade PU. It is thus the first time for such a strain that a PU‐degrading activity is clearly demonstrated.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The strain involving the most significant weight loss on TPU is the strain of Penicillium section Lanata‐Divaricata. Isolated species of Penicillium have been described on PU degradation studies such as Penicillium chrysogenum (Alvarez‐Barragan et al ., ), but to the best of our knowledge, no isolated strains of Penicillium belonging to the section Lanata‐Divaricata has been reported to degrade PU. It is thus the first time for such a strain that a PU‐degrading activity is clearly demonstrated.…”
Section: Discussionmentioning
confidence: 90%
“…Degradation ability of the fungi thus depends on the bonds of the soft segment of the TPU but also on the macromolecular structure. Usually, additional carbon sources such as glucose (Matsumiya et al ., ; Khan et al ., ) or PDB (Alvarez‐Barragan et al ., ) are added to promote the microbial growth and thus, the biodegradation. Regarding the development of an efficient remediation or bio‐recycling process, working without additional carbon source such as glucose, as in our case, is a major financial gain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the moment, many of the promising findings require specialized species and conditions for this [80]. Some have suggested that the white rot fungi might be able to biodegrade PVC [81].…”
Section: Disposal Of Pvcmentioning
confidence: 99%